(untitled) (Nigerian Journal of Physiological Sciences, 2025)
The toxic effect of lead on heart and kidney tissues has been associated with its ability to cause oxidative stress. Azadirachta indica is a versatile medicinal plant with diverse pharmacological potentials. The ameliorative effect of the methanol extract of Azadirachta indica leaf (MEAI) was studied on male Wistar rats exposed to lead acetate (PbAc). Preliminary assays were carried out to assess the total phenolic, total flavonoid, and total flavonol contents of the extract using quantitative phytochemical assays. Cytotoxicity was tested on Vero cells using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide [MTT] assay. Wistar rats were grouped into control, toxicant, and treated groups and administered distilled water, 0.1/0.2% PbAc, and 0.1/0.2% PbAc + 100/200 mg/kg MEAI respectively. Results showed that the total phenolic content of MEAI was negligible while the flavonoid (300±0.12 mg Quercetin/g) and flavonol (80±0.06 mg Rutin/g) contents were significant. LC50 value of MEAI was 0.05 mg/mL. MEAI significantly (p<0.05) increased weight, reduced blood pressure, and increased blood flow/volume in the treated groups. There was significant (p<0.05) reduction in hydrogen peroxide (H2O2) and significant (p<0.05) increase in Nitric oxide (NO) in some of the treated groups. Histopathology revealed that MEAI reduced the infiltration of inflammatory cells in the heart and kidney tissues of the treated groups when compared to those of the lead-exposed untreated groups. There were variations in the expression of cytochrome C in the heart and kidney tissues of the experimental groups compared with the control. This study demonstrates MEAI as a potential drug candidate in the amelioration of lead acetate-induced cardiorenal toxicity by inhibition of oxidative stress, inflammation and by regulating apoptosis.